2012
DOI: 10.5012/bkcs.2012.33.11.3691
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of Hexavalent Chromium Induced by Photolysis of Ferric/tartrate Complex

Abstract: Photocatalytic reduction of hexavalent chromium (Cr(VI)) in ferric-tartrate system under irradiation of visible light was investigated. Effects of light resources, initial pH value and initial concentration of various reactants on Cr(VI) photocatalytic reduction were studied. Photoreaction kinetics was discussed and a possible photochemical pathway was proposed. The results indicate that Fe(III)-tartrate system is able to rapidly and effectively photocatalytically reduce Cr(VI) utilizing visible light. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hexavalent chromium is carcinogenic but the trivalent chromium is less toxic (Feng et al 2012). Hence, it is necessary to reduce the Cr(VI) into Cr(III).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hexavalent chromium is carcinogenic but the trivalent chromium is less toxic (Feng et al 2012). Hence, it is necessary to reduce the Cr(VI) into Cr(III).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical reduction is a simple method with maximum efficiency among the various techniques available. Reduction of Cr(VI) was carried out in the presence of Fe(III)-tartrate catalyst system (Feng et al 2012). Huang et al (2012) reported about the catalytic reduction of Cr(VI) using Pd nanoparticle immobilized electrospun fiber.…”
Section: Introductionmentioning
confidence: 99%